Clinical characteristics of people with diabetic ketoacidosis at a clinic in The Gambia: a retrospective study. Issue 1 (2nd January 2023) - Agboghoroma, Orighomisan F; Jobe, Modou; Forrest, Karen
Abstract : Background: Diabetic ketoacidosis (DKA) remains an important cause of hospitalisation and death in people with diabetes mellitus (DM) living in low- and middle-income countries. The clinical profile of patients with DKA varies, and maybe contributory to the outcomes observed globally. The aim of this study was to describe the clinical characteristics of people with diabetic ketoacidosis (DKA) seen at a clinic in The Gambia during a one-and-a-half-year period. Methods: This was a retrospective chart review that included people with DM who were seen from June 2017 to December 2018 at the Medical Research Council the Gambia at London School of Hygiene and Tropical Medicine. Biodata, anthropometric and admissions data were extracted for all patients from the electronic medical records system. Data were analysed for differences in clinical and biochemical characteristics on admission for DKA. Results: In total, 23 out of 103 admissions for people with DM were for a diagnosis of DKA during the study period. Sixteen of those included were females and the mean age of all patients was 35 ± 13years. Two people had type 1 DM and 15 people were categorised as type 2 DM. DM was diagnosed for the first time during admission for DKA for 12 people and 6 people had confirmed sepsis. There were no significant differences in age at diagnosis of DM or biochemical characteristics. Conclusion: DKA was a common indication for admission for people with DM in the Medical Research Council the Gambia at London School of Hygiene and Tropical Medicine and the majority of patients with DKA had type 2 DM. Further studies are needed to describe DKA in this setting more accurately.